The Effect of Debt To Assets Ratio (DAR) and Debt To Equity Ratio (DER) on Return On Assets (ROA) at PT Phapros Tbk - Intan Sari Budhiarjo; Nurfitriana Nurfitriana; Widya Candra Dewi; Siti Nurcahayati; Sam Cay (Jurnal Ad'ministrare, 2022)
This study aims to determine whether or not there is an effect of Debt to Asset Ratio on Return on Assets and Debt to Equity Ratio on Return on Assets either partially or simultaneously. The object of this research is PT Phapros Tbk. The data used in this open research is secondary data. Using a descriptive research method and the data is quantitative. The variables used are Debt to Assets Ratio (X1) and Debt to Equity Ratio (X2) to Retrun On Assets (Y). From the partial test Debt to Assets Ratio and Debt to Equity Ratio there is no significant effect on Return On Assets. The results of simultaneous hypothesis testing Debt to Assets Ratio and Debt to Equity Ratio together do not significantly influence Return On Assets. The results of the coefficient of determination test (R2) were 0.532 or 53.2%, which means that the contribution made by the Debt to Assets Ratio and Debt to Equity Ratio to Return on Assets reached 53.2% while the remaining 46.8% was influenced by other factors that were not described in this study.